Adobe InDesign Classroom in a book 2025 release the official training workbook from Adobe - Anton, Kelly Kordes; DeJarld, Tina (Adobe Press, 2025)
Adobe InDesign Classroom in a Book 2025 Release contains 15 lessons that use real-world, project-based learning to cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. For beginners and experienced users alike, you can follow the book from start to finish or choose only those lessons that interest you.
Includes index
Keywords: Adobe InDesign (Electronic resource); Desktop publishing